2017
DOI: 10.1136/openhrt-2017-000630
|View full text |Cite
|
Sign up to set email alerts
|

Left ventricular longitudinal systolic function analysed by 2D speckle-tracking echocardiography in heart failure with preserved ejection fraction: a meta-analysis

Abstract: BackgroundThe purpose of this meta-analysis was to confirm if the global longitudinal systolic function of the left ventricle (LV) is altered in patients with heart failure with preserved ejection fraction (HFpEF).MethodsWe searched in different databases (Medline, Embase and Cochrane) studies that analysed LV global longitudinal systolic strain (GLS) in patients with HFpEF and in controls (such as healthy subjects or asymptomatic patients with arterial hypertension, diabetes mellitus or coronary artery diseas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
63
2
6

Year Published

2019
2019
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 88 publications
(77 citation statements)
references
References 37 publications
6
63
2
6
Order By: Relevance
“…13 Previous reports demonstrated that LVGLS related to exercise capacity through the poor contractile reserve during exercise. [14][15][16] Actually, in the present study, LVGLS in the G < 50 was worst compared to the other two groups. LVGLS was significantly impaired in the G < 50 than in other two groups.…”
Section: The Ability Of E/lvgls To Detect Impaired Exercise Capacitycontrasting
confidence: 53%
See 1 more Smart Citation
“…13 Previous reports demonstrated that LVGLS related to exercise capacity through the poor contractile reserve during exercise. [14][15][16] Actually, in the present study, LVGLS in the G < 50 was worst compared to the other two groups. LVGLS was significantly impaired in the G < 50 than in other two groups.…”
Section: The Ability Of E/lvgls To Detect Impaired Exercise Capacitycontrasting
confidence: 53%
“…This finding was concordant with previous reports. [14][15][16] The use of β blocker and diuretics was most frequent, and NT pro-BNP was highest in the G < 50 among groups. Therefore, we tested the influence of these medical therapies and NT-proBNP on exercise capacity by multivariate analysis.…”
Section: The Ability Of E/lvgls To Detect Impaired Exercise Capacitymentioning
confidence: 99%
“…In our study, we categorized the included patients into three subgroups according to LAVI and NT‐proBNP level and focused on the potential predictive value of LV deformation parameters and RDW in HFpEF. A meta‐analysis analyzing 2284 patients with HFpEF and 2302 controls confirmed that the longitudinal systolic function of the LV is dramatically impaired in a large proportion of patients with HFpEF . In our study, we found that in definite HFpEF patients who had the largest LAVI and highest NT‐proBNP levels, the absolute values of GLS, GRS, GCS, and GAS were all significantly lower than those in the other two subgroups, and the RDW value was significantly higher than that in the rest subgroups.…”
Section: Discussionmentioning
confidence: 99%
“…214 Reduced LV longitudinal systolic strain and LV early diastolic strain rate have both been identified in HFpEF. 19,215,216 Impaired GLS predicts HF hospitalization, cardiovascular death, or cardiac arrest. 216,217 It correlates with invasive measurements of LV stiffness and with NP levels.…”
Section: Minor Criterion∶ Gls < 16%mentioning
confidence: 99%